2014
DOI: 10.1016/j.bbrc.2014.09.072
|View full text |Cite
|
Sign up to set email alerts
|

Redox-sensitive residue in the actin-binding interface of myosin

Abstract: We have examined the chemical and functional reversibility of oxidative modification in myosin. Redox regulation has emerged as a crucial modulator of protein function, with particular relevance to aging. We previously identified a single methionine residue in Dictyostelium discoideum (Dicty) myosin II (M394, near the myosin cardiomyopathy loop in the actin-binding interface) that is functionally sensitive to oxidation. We now show that oxidation of M394 is reversible by methionine sulfoxide reductase (Msr), r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Is it possible that estradiol acts by influencing other phosphorylation targets involved in myosin-based contractility, such as myosin-binding protein C [28], titin, or troponin [29]? What about other post-translational protein modifications, such as oxidation [12,30]? What are the other components in the estradiol signaling pathway that eventually lead to regulation of SRX [31,32]?…”
Section: Discussionmentioning
confidence: 99%
“…Is it possible that estradiol acts by influencing other phosphorylation targets involved in myosin-based contractility, such as myosin-binding protein C [28], titin, or troponin [29]? What about other post-translational protein modifications, such as oxidation [12,30]? What are the other components in the estradiol signaling pathway that eventually lead to regulation of SRX [31,32]?…”
Section: Discussionmentioning
confidence: 99%
“…Both NM- and muscle- myosin II have been proposed to be redox sensors within cells, because both are reversibly oxidized and this oxidation inhibits their interaction with actin and their ATPase activity [96]. This regulatory oxidation occurs at Met394 of protist NM-myosin II [97], which is equivalent to a cysteine that is glutathyolated in mammalian cardiac and skeletal muscle myosin II [96].…”
Section: The Actin Cytoskeleton As a Target Of Oxidantsmentioning
confidence: 99%
“…This regulatory oxidation occurs at Met394 of protist NM-myosin II [97], which is equivalent to a cysteine that is glutathyolated in mammalian cardiac and skeletal muscle myosin II [96]. However, Fiaschi and colleagues [98], who examined myosin oxidation in the context of cell spreading, suggested that only NM-MHC is under redox control.…”
Section: The Actin Cytoskeleton As a Target Of Oxidantsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, Met oxidation and subsequent reduction by Met sulfoxide reductase have far-reaching implications in metabolic, cardiovascular, neurological, and immune related dysfunction [10, 11, 12]. We have identified specific Met residues in proteins as targets of oxidation in muscle contractile and regulatory proteins [13, 14, 15]. Met oxidation has been proposed as a mechanism through which the muscle cell responds to oxidative stress by modulating metabolism and energy utilization [16].…”
Section: Introductionmentioning
confidence: 99%